Part four of the Rhodes University Skymap Program - Wright, Michael Robert (Rhodes University, Faculty of Science, Department of Physics, 1989)
The results of the fourth part of the Rhodes University Skymap Program are presented. The observations cover the area of sky between right ascension 14h00m and 02h30m and declination -26â ° and + 13â ° at a frequency of 2.3 GHz. Contour maps of this region, with a resolution of 0.38â °, are presented. Various methods of reducing the effect of the Galactic disc emission are analyzed. The results demonstrate the effectiveness of one of these methods in the production of a flat base level. The filamentary structure of the North Polar Spur is enhanced and results are obtained which support current theories of the origin of this object. The HII region surrounding Ophiuchi is examined in detail. A number of parameters are derived for the HII region. The spur associated with the HII region S54 is also examined. A listing of 1105 point sources appearing in the maps is presented. The limiting flux density of this listing is 0.5 Jy
Keywords: Southern sky (Astronomy); Radio astronomy